PROMOSI FOOD AND BEVERAGE DI GRAND CENTRAL HOTEL PEKANBARU - Ratna Sari Pratiwi; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The f&b promotion mix and its implementation at Grand Central Hotel Pekanbaru are more focused on discussing the f&b promotion mix at Grand Central Hotel Pekanbaru. Identify and describe the implementation of the food and beverage promotion mix at Grand Central Hotel Pekanbaru. This study uses a descriptive (qualitative)  method,  according  to  Sugiyono  (2008)  “is  an  analytical  method based on post-positivism philosophy, used to examine natural objects, the researcher as the key instrument. The results of his research emphasize meaning rather than generalizations. The reason the author chooses the qualitative method is considering that this method is quite capable of explaining things that include a collection  of  data  obtained  from  interviews  with  language  that  is  easy  to understand and understand. Grand Central Hotel Pekanbaru's promotional strategies are Advertising, personal selling, direct marketing, publicity and sales promotion. Of the five promotional strategy steps that have been carried out by Grand Central Hotel Pekanbaru, researchers see and feel that the promotion of Food and Beverage through advertisements on social media is the most attractive to guests or consumers. according to Philip Kotler, namely advertising, personal selling, direct marketing, publicity and sales promotion. The Food and Beverage Promotion  Strategy  carried  out  by  Grand  Central  Hotel  Pekanbaru  is  quite effective and gets a positive response from guests or consumers and is able to increase hotel profits. Keywords : Promotion mix, food and beverage, hotel